â€œYANG-TETAPâ€ DAN â€œYANG-BERUBAHâ€ DALAM PERSPEKTIF METAFISIKA PANCASILA - Pitojo, Djoko (Jurnal Filsafat "WISDOM", 2007)
The paper will tries to review classical debate about â€œthe stableâ€ and â€œthe changeâ€ and discuss every notion in their variants. Description about the debate among philosophers will express chronologically as possible. Last but not least, it tries to express â€œthe stableâ€ and â€œthe changeâ€ in Philosophy of Pancasila perspective. Pancasila, in its position as a genetivus objectivus, is very interesting to interpreted continuously; in order to do it, we must neither to maintain â€œthe stabileâ€ as a â€œgloriousâ€ in the one hand nor merely want to make it â€œchangeâ€ in the other hand. For both attitudes are naÃ¯ve and irresponsible. Pancasila, as a life symbol, must be actualized and interpreted openly, dialogically and there is no place for monopoly in interpretation. While, Pancasila as a genetivus subjectivus, give answer to the developing and management of state problems, unavoidably, the changes are always as assumption. â€œThe stableâ€ is â€œbeingâ€ itself with its identity and developing; and that is meaning its existence. The ethical implication, therefore, is commitment to values inhering on the existence of being itself. â€œThe changeâ€ is the way to handle of being and its technical management.